Analisis Deiksis dalam Tulisan Kolom Opini Situs Mojok.co - M. Furqon Al Maarif; Alfi Nur Hasanah; Ike Nur Baeti; Muhammad Yusuf Zanuar; Sumarwati Sumarwati; Andayani Andayani (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2023)
Language is a tool used by humans in communicating. The theory of language develops and becomes the talk of experts. Pragmatics, as a linguistic discipline, has clear differences from other linguistic disciplines, both in terms of terminology and research focus. Pragmatics focuses on the goals that speakers want to achieve through their communication. Pragmatics has another derivative, one of which exists. The research entitled “Analysis of Diexis in Writing Opinion Columns on the Mojok.co Site aims to analyze the use of diexist in the form of persona diexist, place or space diexist, time diexist and discourse diexist. This research use desciptive qualitative approach. The data collection technique used in this study was reading and taking notes. Based on the results of the study, it was found that there is the use of persona diexis, place or space diexis, time diexis and discourse diexis in writing uploaded in the Opinion Column of Mojok.co